Christensen updates disruption theory. Issue 2 (21st March 2016) - Denning, Stephen
Abstract : Purpose: – Recently, observers of the battle between incumbents and challengers have turned the field of disruptive innovation theory into contested territory. What strategies work for defenders and attackers? Design/methodology/approach: – For an update the author asked the opinion of the world's foremost authority, Harvard professor Clayton Christensen. Findings: – According to Christensen, "We discovered that there are three types of innovations, only two of which we had caught in the [original] theory of disruption. Practical implications: – The only permanent way out of the innovator's dilemma is to change the game being played and adopt a new corporate focus in which innovation is a necessity, not an option. Originality/value: – The article updates and broadens disruption theory. Disruption, as Christensen defines it, is a theory of competitive response.